Gender Analysis of Children’s Activities in Pakistan (The Pakistan Development Review, 2008)
This paper estimates gender differences in children’s time allocation among four ordered options. It analyses the sample of boys and girls separately through a series of probit models using primary data. We compare the socio-economic determinants of boys’ and girls’ activities. The results suggest that boys are more likely to go to school as compared to girls with the increase in their age. The provision of schooling as an instrument to decrease child labour and home-care would affect boys more than girls. To make the adults literate (five years of education) only is not enough to eliminate the gender gap in schooling; a greater number of years of adult education is necessary. The female adult education may be devised to eliminate gender discrimination in child schooling. In the larger households, girls drop out of school and are absorbed in the labour market earlier than boys. The results further suggested that the use of resources is significantly different for boys’ and girls’ welfare. Thus, we conclude that girls can be a better target for increase in the welfare of all children in Pakistan.